Method for reducing perfluorinated and polyfluorinated alkyl substances in water by adsorption enrichment-desorption analysis-hydration electrons

By adsorbing a fluorine-doped CTF material and using a mixed solvent system containing saturated KI solution to desorb PFAS in water, combined with hydrated electron reduction technology, the problems of low concentration PFAS removal efficiency and secondary pollution are solved, and efficient and harmless PFAS treatment effect is achieved.

CN119528260AActive Publication Date: 2025-02-28NANJING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311112498.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove perfluoro and polyfluoroalkyl substances (PFAS) in low-concentration water bodies, and secondary pollution is often caused during the regeneration of adsorbents.

Method used

Fluorine-doped covalent triazine-based frame (CTF) material is used as the adsorbent, and PFAS is adsorbed through electrostatic, hydrophobic and carbon fluorine chains on the surface of the material, and a mixed solvent system containing saturated KI solution is used for desorption. Finally, PFAS is completely removed by hydration electron reduction technology.

Benefits of technology

Efficient removal of low-concentration PFAS is achieved, with a removal rate of about 4 times that of existing CTF materials, and secondary pollution is avoided, and the harmless treatment of PFAS is completed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528260A_ABST
    Figure CN119528260A_ABST
Patent Text Reader

Abstract

The invention discloses a method for reducing perfluoro and polyfluoroalkyl substances in water through adsorption enrichment-desorption desorption-hydration electrons. The method comprises the following steps: adsorbing PFAS in water by using a fluorine-doped covalent triazine porous material; desorbing the fluorine-doped CTF material adsorbing the PFAS in the previous step by adopting a mixed solvent system containing a saturated KI solution, transferring the desorbed high-concentration PFAS solution into a quartz reactor, adding Na2SO3, and carrying out reduction defluorination by generating hydration electrons through ultraviolet irradiation. By utilizing the combined technology, low-concentration PFAS in wastewater / environmental water can be effectively enriched, a single pollutant solution and a desorbed solution can be subsequently recycled, PFAS in the desorbed solution can be reduced by utilizing hydration electrons for mixed pollutants, and a subsequent biological treatment process is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorption and reduction defluorination method for low-concentration perfluoro and polyfluoroalkyl substances in water, belonging to the technical field of organic pollutant treatment. Background Art

[0002] Innovative and low-cost methods to remove and degrade per- and polyfluoroalkyl substances (PFAS) in water have become a current research hotspot. Advanced oxidation processes (AOPs) have been widely studied for PFAS degradation, but the strong CF bond (536 kJ / mol) hinders the free radical oxidation of PFAS molecules, especially the hydroxyl radical (·OH) which is inert to PFAS. Various photocatalysts have been developed to promote the oxidative destruction of PFAS, such as TiO2, In2O3, Gd2O3 and SiC / graphene, but these photocatalysts are usually used to treat bulk water, which usually consumes excessive energy due to the large treatment volume. Studies have shown that among the existing technologies for removing or separating PFAS from environmental samples, adsorption is the simplest, fastest and most effective measure, especially for low-concentration PFAS water. At present, a variety of adsorbents such as CTAB micelle-encapsulated SiO2, cross-linked chitosan beads, anion exchange resins, etc. have been used to remove PFAS from water. These adsorbents are mainly based on hydrophobic interactions, electrostatic attraction and ion exchange to identify PFAS. However, the organic solvents used in the adsorbent regeneration process often cause secondary pollution.

[0003] The treatment of the desorption liquid after the adsorbent adsorbs PFAS becomes an important part of whether PFAS can be completely removed. Therefore, the present invention adopts a method of adsorption enrichment-desorption analysis-hydration electron reduction of PFAS in water to completely remove PFAS in the water to be treated. Covalent triazine-based framework (CTF) is a new type of non-swelling polymer, which is synthesized by ionic thermal trimerization of aromatic nitriles, and has a very large specific surface area, uniform and rigid pore structure, high chemical and thermal stability and relatively low cost. PFAS has the characteristics of hydrophobicity and oleophobicity. In water, the carbon fluorine chain not only repels water molecules but also has no affinity for hydrocarbon substances, and there is a tendency for the carbon fluorine chains to agglomerate with each other. Therefore, the "like dissolves like" principle can be used to carry out organic fluorination modification on the surface of the CTF adsorbent, and the carbon fluorine chain on the surface of the material can be used to adsorb PFAS in water. The hydrophobic and oleophobic effect of the carbon fluorine chain can repel hydrocarbon organic matter, thereby achieving the purpose of selectively removing PFAS. A mixed solvent system containing a saturated KI solution is used to desorb the fluorine-doped CTF material that has adsorbed PFAS, and then the desorbed PFAS is reduced using hydrated electrons. This can effectively remove PFAS from the water to be treated, while efficiently treating PFAS and avoiding secondary pollution.

[0004] The Chinese patent application number 201710122426.8 discloses a method for photocatalytic degradation of perfluorinated compounds. The patent prepares a dual-model mesoporous SiO2 material BMMs, uses phosphotungstic acid as the active component, and prepares the HPW / BMMs catalyst by an impregnation method. The catalyst is added under ultraviolet light to achieve the degradation and defluorination of perfluorinated compounds. The system has poor treatment effect on low-concentration perfluorinated compounds. A 10 mg / L PFAS solution can only remove 40% after irradiation under ultraviolet light for 4 hours.

[0005] The Chinese patent application number 201710098400.4 discloses a sludge-based activated carbon with high efficiency in adsorbing PFAS, as well as its preparation method and application. The patent prepares sludge-based activated carbon through drying, activation, high-temperature carbonization treatment, acid leaching, washing and drying, and the adsorption removal rate of low-concentration PFAS is as high as 99.9% and 71.0%. However, the effective pH range of the adsorbent is narrow, the reusability is poor, and the activated carbon has a relatively poor adsorption effect on hydrophobic and lipophobic PFCs.

[0006] A Chinese patent with application number 202210813328.X discloses the preparation of a cerium-doped highly crystalline carbon nitride adsorbent and its application in the adsorption of emerging pollutants. The cerium-doped highly crystalline carbon nitride adsorbent prepared by this patent has an increased specific surface area, an increased number of adsorption active sites, and improved adsorption performance and rate, but there is a problem of secondary pollution caused by metal dissolution.

[0007] The Chinese patent application number 202210339442.3 discloses an electrochemical method for activating persulfate and O2 to synergistically degrade perfluorinated compounds. The patent uses a one-step synthesis method to in-situ form a bimetallic carbon aerogel electrode doped with iron and nickel. On the surface of the electrode, a 2-electron oxygen reduction reaction (ORR) can occur in situ to produce H2O2. At the same time, the abundant metal active sites on the electrode surface can activate peroxymonosulfonate (PMS) to produce sulfate radicals (SO4. - ), and the perfluorinated compounds are degraded by the synergistic action of these two free radicals at the cathode. The electrode sheet of this system is prone to metal dissolution, causing secondary pollution, and has poor reusability. Summary of the invention

[0008] For low-concentration PFAS water bodies, the present invention aims to provide a method for adsorption enrichment-desorption analysis-hydrated electron reduction of PFAS, which can solve the technical problems of low-concentration PFAS water body treatment to a certain extent.

[0009] The technical solution to achieve the purpose of the present invention is: a method for adsorption enrichment-desorption analysis-hydration electron reduction of per- and polyfluoroalkyl substances in water, comprising:

[0010] (1) Using fluorine-doped CTF materials to adsorb low-concentration PFAS in the water to be treated;

[0011] (2) desorbing the fluorine-doped CTF material adsorbing PFAS in step (1) using a mixed solvent system containing a saturated KI solution;

[0012] (3) Using hydrated electrons to reduce the desorbed high concentration PFAS.

[0013] Preferably, the fluorine-doped CTF material is prepared by the following steps: tetrafluoroterephthalonitrile and ZnCl2 are fully mixed by grinding, vacuum calcined at 400-500°C for 35-40h, washed, dried and then sieved.

[0014] Specifically, the mass ratio of tetrafluoroterephthalonitrile to ZnCl2 is 1:6.

[0015] Specifically, after drying, the mixture is sieved through a 200-300 mesh sieve.

[0016] Preferably, in step (1), the fluorine-doped CTF material is placed in the water to be treated, 5 mg of the fluorine-doped CTF material is added to every 30 to 150 ml of the water to be treated, and the adsorption time is more than 4 hours.

[0017] Preferably, the concentration of PFAS in the water to be treated is 10 to 250 ppm.

[0018] Preferably, in step (2), a mixed solvent system containing a saturated KI solution is used to desorb the fluorinated CTF material adsorbed with PFAS in step (1), and the process is as follows: the fluorinated CTF material adsorbed with PFAS in step (1) is placed in a mixed solvent system containing a saturated KI solution, and desorbed under shaking conditions for more than 4 hours, and 5 mg of the fluorinated CTF material adsorbed with PFAS is added to every 30 to 150 ml of the mixed solvent system containing a saturated KI solution.

[0019] Preferably, in the mixed solvent system containing the saturated KI solution, the mixed solvent consists of methanol and water in a volume ratio of 7:3, and the concentration of the saturated KI solution in the system is 1 vol%.

[0020] Preferably, in step (3), hydrated electrons are used to reduce the desorbed high-concentration PFAS, and the process is as follows: the PFAS solution obtained by adding water to the desorbed PFAS is placed in a quartz glass container, and Na2SO3 is added thereto under UV light to reduce the PFAS. The concentration of the PFAS solution is 30 to 100 mg / L, and 100 to 600 mg of Na2SO3 is added to every 400 ml of PFAS solution.

[0021] Specifically, the power of the UV lamp is above 10W.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] 1. The F-CTF material of the present invention utilizes electrostatic effect, hydrophobic effect and the carbon fluorine chain on the surface of the material to have a strong adsorption effect on PFAS, and the removal rate of PFAS in sewage is about 4 times that of the existing CTF material.

[0024] 2. According to the embodiment of the present invention, the desorbed PFAS can be treated to avoid secondary pollution and complete the harmless treatment of PFAS.

[0025] 3. Utilize KI in a mixed solvent system containing a saturated KI solution as a co-activator for hydrated electrons to efficiently reduce the desorbed PFAS, thereby achieving the goal of saving resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the SEM image of the F-CTF of the present invention.

[0027] Figure 2 is the XRD pattern of the CTF of the present invention.

[0028] Figure 3 This is a schematic diagram comparing the adsorption effects of F-CTF material and other CTF materials on PFAS in treated water in an application example of the present invention, wherein the inset is a schematic diagram comparing the adsorption effects of F-CTF material and other CTF materials on PFAS in treated water within one hour.

[0029] Figure 4 This is a schematic diagram of the adsorption and removal effect of PFAS after six consecutive regenerations of F-CTF in an application example of the present invention.

[0030] Figure 5 This is an application example of the present invention, and shows a curve of PFAS concentration change when sodium sulfite is added and UV irradiation is applied.

[0031] Figure 6 This is a flow chart of the method for adsorption enrichment-desorption analysis-hydrated electron reduction of per- and polyfluoroalkyl substances in water according to the present invention. Specific implementation method:

[0032] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions.

[0033] The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. It should be noted that the terms "first", "second", etc. used herein are only for convenience of description and should not be construed as indicating or implying relative importance, nor should they be construed as having a sequential relationship. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0034] The following inventions and ideas are the basis for the inventor to make the present invention:

[0035] CTF has a very large specific surface area, a uniform and rigid pore structure, high chemical and thermal stability, and a relatively low cost. PFAS has hydrophobic and oleophobic properties. In water, the carbon fluoride chains repel water molecules and are not affinity with hydrocarbon substances, and the carbon fluoride chains tend to agglomerate with each other. Therefore, the "like dissolves like" principle can be used to perform organic fluorination modification on the surface of the CTF adsorbent, and the carbon fluoride chains on the surface of the material can be used to adsorb PFAS in water. The hydrophobic and oleophobic effects of the carbon fluoride chains can repel hydrocarbon organic matter, thereby achieving the purpose of selectively removing PFAS.

[0036] The regeneration of the adsorbent usually requires organic solvents, such as methanol, ethanol, etc. The eluted PFAS still exists in the regeneration liquid. Improper handling will cause secondary pollution. Taking this problem into consideration, the present invention provides a method for adsorption and reduction defluorination, in which the desorbed PFAS is placed in a UV quartz glass reactor, and sodium sulfite is added. The hydrated electrons generated by sodium sulfite under UV irradiation can efficiently reduce PFAS, thereby achieving complete removal of PFAS in the water to be treated.

[0037] PFAS is desorbed using a mixed solvent system containing a saturated KI solution. In the field of hydrated electronics, KI can be used as a co-activator for Na2SO3. Compared with the use of Na2SO3 or KI alone, it has a higher reduction efficiency and can reduce PFAS more efficiently and quickly.

[0038] The following examples are provided to facilitate a better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0039] The above-mentioned method of adsorbing and reducing low-concentration PFAS in water will be explained with specific examples.

[0040] Example 1

[0041] The preparation method of the F-CTF adsorbent of the present invention comprises the following specific steps:

[0042] (1) 1 g of tetrafluoroterephthalonitrile and 6.82 g of ZnCl2 were thoroughly mixed by grinding, and the mixture was transferred to a quartz ampoule.

[0043] (2) After evacuation, the tube is sealed and calcined in a muffle furnace at 400° C. for 40 hours, and then cooled to room temperature.

[0044] (3) The calcined product was stirred and washed with 1 mol / L hydrochloric acid for 48 h, then washed with deionized water until the solution was neutral, and dried at 60° C. to obtain material F-CTF.

[0045] Comparative Example 1

[0046] The preparation method of FUM-CTF adsorbent using trans-butene dinitrile as a precursor comprises the following specific steps:

[0047] (1) 0.39 g of fumaronitrile and 6.82 g of ZnCl2 were thoroughly mixed by grinding, and the mixture was transferred to a quartz ampoule.

[0048] (2) After evacuation, the tube is sealed and calcined in a muffle furnace at 400° C. for 40 hours, and then cooled to room temperature.

[0049] (3) The calcined product was stirred and washed with 1 mol / L hydrochloric acid for 48 h, then washed with deionized water until the solution was neutral, and dried at 60° C. to obtain the material FUM-CTF.

[0050] Comparative Example 2

[0051] The preparation method of the DCB-CTF adsorbent using terephthalonitrile as a precursor comprises the following specific steps:

[0052] (1) 0.64 g of terephthalonitrile and 6.82 g of ZnCl2 were thoroughly mixed by grinding, and the mixture was transferred to a quartz ampoule.

[0053] (2) After evacuation, the tube is sealed and calcined in a muffle furnace at 400° C. for 40 hours, and then cooled to room temperature.

[0054] (3) The calcined product was stirred and washed with 1 mol / L hydrochloric acid for 48 h, then washed with deionized water until the solution was neutral, and dried at 60° C. to obtain the material DCB-CTF.

[0055] The structural characteristics of the adsorbents obtained in Example 1 and Comparative Examples 1-2 include:

[0056] (1) Morphology observation

[0057] Scanning electron microscopy (SEM) was used to characterize the morphology of F-CTF. Figure 1As shown, aggregates of hierarchical CTF nanoscale objects, F-CTF consists of irregular rectangular aggregates.

[0058] (2) Crystal form

[0059] XRD spectra of CTF materials prepared with different precursors are shown in Figure 2. Figure 2 As shown in the figure, it can be seen that CTF has an obvious characteristic peak at 2θ of 7.2°, reflecting the (100) crystal plane of the hexagonal structure of the triazine functional group; there is an obvious broad peak at 26.2°, which reflects the (001) crystal plane of the aromatic layer structure.

[0060] Application Example 1

[0061] This application example mainly examines the adsorption equilibrium time and adsorption rate of PFAS in water by the F-CTF adsorbent prepared in Example 1, the FUM-CTF adsorbent prepared in Comparative Example 1, and the DCB-CTF adsorbent prepared in Comparative Example 2. The specific steps are as follows:

[0062] First, 5 mg of the corresponding adsorbent was weighed into a 50 ml polypropylene centrifuge tube, and 30 ml of 250 mg / L PFAS was added to the centrifuge tube. The tube was shaken at 160 r / min at 25 °C. 1 ml of each adsorbent was sampled at 0, 0.5, 1, 2, 3, 5, 7, 10, 15, 30, 45, 60, 90, 120, 180, 240, and 360 min at the beginning of the experiment. The sample was filtered with a filter membrane with a pore size of 0.22 μm to remove the adsorbent, and the concentration of PFAS in the sample was determined by high performance liquid chromatography. The adsorption amount q at time t was t Calculated using the following formula:

[0063] q t =V×(C0-C t ) / m

[0064] Where V is the volume of the solution (L), C0 is the initial concentration of the PFAS solution (mg / L), and C t is the solution concentration at time t (mg / L), and m is the mass of the added adsorbent (g).

[0065] Depend on Figure 3It can be seen that compared with the FUM-CTF adsorbent prepared in Comparative Example 1 and the DCB-CTF adsorbent prepared in Comparative Example 2, the F-CTF adsorbent synthesized in Example 1 reaches adsorption equilibrium within 120 minutes for PFAS with a concentration of 250ppm in the solution, and the adsorption amount is significantly higher than that of the control group, reaching an adsorption amount of 580mg / g. This is mainly attributed to the organic fluorination modification on the surface of the CTF adsorbent. PFAS has hydrophobic and oleophobic properties. In water, the carbon fluoride chains both repel water molecules and are not affinity with hydrocarbon substances, and the carbon fluoride chains tend to agglomerate with each other. Organic fluorination modification is carried out on the surface of the CTF adsorbent, and the carbon fluoride chains on the surface of the material are used to adsorb PFAS in water, so as to achieve the purpose of selective adsorption of PFAS.

[0066] Application Example 2

[0067] This application example mainly examines the reuse effect of the F-CTF adsorbent prepared in Example 1, and the specific steps are as follows:

[0068] (1) First, 5 mg of F-CTF adsorbent was weighed into a 30 ml polypropylene centrifuge tube (the F-CTF adsorbent subjected to adsorption-desorption in Application Example 1), and 20 ml of 250 mg / L PFAS was added to the centrifuge tube. The tube was shaken at 160 r / min at 25°C. After adsorption for 4 h, 1 ml of the F-CTF adsorbent was sampled. The sample was filtered with a filter membrane with a pore size of 0.22 μm to remove the adsorbent, and the PFAS concentration in the sample was determined by high performance liquid chromatography. The adsorption amount q at time t was t Calculated using the following formula:

[0069] q t =V×(C0-C t ) / m

[0070] Where V is the volume of the solution (L), C0 is the initial concentration of the PFAS solution (mg / L), and C t is the solution concentration at time t (mg / L), and m is the mass of the added adsorbent (g).

[0071] (2) The reacted F-CTF material was placed in 20 ml of a mixed solvent system of methanol and water containing 1 vol% saturated KI solution, and oscillated in a constant temperature oscillator at a speed of 160 r / min for 4 h. The centrifuge tube was then placed in a high-speed centrifuge and centrifuged at a speed of 14500 rpm for 10 min. The desorbed F-CTF material was taken out, washed and dried, and PFAS at a concentration of 250 ppm was re-adsorbed. The above desorption was repeated 6 times.

[0072] The adsorption effect of the adsorbent after six cycles is as follows: Figure 4 As shown by Figure 4It can be seen that after three adsorption cycles, the removal rate of PFAS in water by F-CTF decreased slightly, about 15% compared with the first adsorption. The reason for the decrease in adsorption amount may be that a small amount of PFAS failed to desorb during the desorption and regeneration process, and this part of PFAS occupied a certain number of adsorption sites. F-CTF regenerated by a mixed solvent system of methanol and water containing 1 vol% saturated KI solution showed strong stability in six adsorption desorption and regeneration cycle experiments, showing the high availability and stability of F-CTF materials.

[0073] Application Example 3

[0074] Combination Figure 6 The present invention provides a method for adsorption enrichment-desorption analysis-hydration electron reduction of perfluoroalkyl substances and polyfluoroalkyl substances in water, comprising:

[0075] (1) Adsorbing PFAS in the water to be treated using the F-CTF material prepared in Example 1;

[0076] (2) desorbing the fluorine-doped CTF material adsorbed with PFAS in step (1) using a mixed solvent system of methanol and water containing 1 vol% saturated KI solution;

[0077] (3) Using hydrated electrons to reduce the desorbed PFAS, the specific process is as follows:

[0078] The desorption solution of F-CTF material was placed in a UV quartz glass reactor, nitrogen was introduced into the reactor for 30 minutes, 2 mmol of sodium sulfite was added, and after the solution was stirred evenly, a 10W UV lamp was turned on. 1 ml of samples were taken at 0, 1, 3, 5, 7, 10, 15, 20, and 30 minutes after the start of the experiment. The samples were filtered through a filter membrane with a pore size of 0.22 μm to remove the adsorbent, and the concentration of PFAS in the samples was determined by high performance liquid chromatography. The experimental results are shown in Figure 2. Figure 5 shown.

[0079] Comparative application example 1

[0080] (1) Adsorbing PFAS in the water to be treated using the F-CTF material prepared in Example 1;

[0081] (2) desorbing the fluorine-doped CTF material adsorbed with PFAS in step (1) using a mixed solvent system of methanol and water containing 1 vol% saturated NaCl solution;

[0082] (3) Utilize hydrated electrons to reduce the desorbed PFAS. The specific process is as follows: Place the desorption solution of the F-CTF material in a UV quartz glass reactor, introduce nitrogen into the reactor for 30 minutes, add 5mmol / L sodium sulfite, and after the solution is stirred evenly, turn on the 10W UV lamp. Take 1ml of samples at 0, 1, 3, 5, 7, 10, 15, 20, and 30 minutes after the start of the experiment. Filter the sample with a filter membrane with a pore size of 0.22μm to remove the adsorbent, and then determine the concentration of PFAS in the sample by high performance liquid chromatography. The experimental results are as follows: Figure 5 shown.

[0083] UV / sulfite systems have been shown to produce highly reducing e aq - , e aq - PFAS can be reduced efficiently, and potassium iodide can be used as a co-activator for sulfite to increase the yield of hydrated electrons, thereby reducing PFAS more efficiently, such as Figure 5 As shown, when 5mmol / L sodium sulfite was added to the desorption solution containing 50ppm, the removal rate of PFAS within 30min was only 50%. The fluorine-doped CTF material that adsorbed PFAS was desorbed using a mixed solvent system of methanol and water containing 1vol% saturated KI solution. When the PFAS concentration in the desorption solution was 50ppm, the KI concentration was calculated to be about 3mmol / L. When 2mmol / L sodium sulfite was added to the desorption solution containing 3mmol / L potassium iodide, the removal rate of PFAS reached 95% within 30min, which was significantly better than the removal effect of sodium sulfite alone. This is mainly attributed to the fact that potassium iodide, as a co-exciter of sodium sulfite, can increase the yield of hydrated electrons, thereby increasing the reduction efficiency of PFAS.

[0084] The present invention provides a method for adsorption enrichment-desorption analysis-hydrated electron reduction of PFAS for low-concentration PFAS water bodies, innovatively combining adsorption and advanced reduction methods. Compared with other treatment methods, it can efficiently enrich low-concentration PFAS with a removal efficiency of up to 90%, and subsequently use hydrated electron reduction for defluorination, efficiently treat mixed pollutants, and solve the problem of secondary pollution of the desorption liquid.

Claims

1. A method for adsorption enrichment-desorption analysis-hydration electron reduction of per- and polyfluoroalkyl substances in water, characterized in that: include: (1) Using fluorine-doped CTF materials to adsorb low-concentration PFAS in the water to be treated; (2) using a mixed solvent system containing a saturated KI solution to desorb the fluorine-doped CTF material adsorbing PFAS in step (1); (3) Using hydrated electrons to reduce and desorb high concentrations of PFAS.

2. The method according to claim 1, characterized in that The fluorine-doped CTF material is prepared by the following steps: tetrafluoroterephthalonitrile and ZnCl2 are fully mixed by grinding, calcined in vacuum at 400-500°C for 35-40h, washed, dried and then sieved.

3. The method according to claim 2, characterized in that The mass ratio of tetrafluoroterephthalonitrile to ZnCl2 is 1:

6.

4. The method according to claim 2, characterized in that After drying, pass through a 200-300 mesh sieve.

5. The method according to claim 1, characterized in that In step (1), the fluorine-doped CTF material is placed in the water to be treated, and 5 mg of the fluorine-doped CTF material is added to every 30-150 ml of the water to be treated, and the adsorption time is more than 4 hours.

6. The method according to claim 1, characterized in that The concentration of PFAS in the water to be treated is 10~250ppm.

7. The method according to claim 1, characterized in that In step (2), a mixed solvent system containing a saturated KI solution is used to desorb the fluorinated CTF material adsorbed with PFAS in step (1). The process is as follows: the fluorinated CTF material adsorbed with PFAS in step (1) is placed in a mixed solvent system containing a saturated KI solution, and desorbed under shaking conditions for more than 4 hours. 5 mg of the fluorinated CTF material adsorbed with PFAS is added to every 30 to 150 ml of the mixed solvent system containing a saturated KI solution.

8. The method according to claim 1, characterized in that In the mixed solvent system containing the saturated KI solution, the mixed solvent consists of methanol and water in a volume ratio of 7:3, and the concentration of the saturated KI solution in the system is 1 vol%.

9. The method according to claim 1, characterized in that In step (3), hydrated electrons are used to reduce the desorbed high-concentration PFAS. The process is as follows: the PFAS solution obtained by adding water to the desorbed PFAS is placed in a quartz glass container, and Na2SO3 is added thereto under UV light to reduce the PFAS. The concentration of the PFAS solution is 30~100 mg / L, and 100~600 mg of Na2SO3 is added to every 400 ml of PFAS solution.

10. The method according to claim 9, characterized in that The power of the UV lamp is above 10W.

Citation Information

Patent Citations

  • Application of graphite-phase carbon nitride in removing of perfluorocaprylic acid in water

    CN108144572A

  • Fluorine-containing metal-organic framework, preparation method thereof and application in adsorption of perfluorooctanoic acid

    CN110237819A

  • One-dimensional organic nanomaterial and preparation method thereof

    CN112851938A

  • Systems and methods for degrading per- and poly-fluoroalkyl substances

    US20220371920A1